(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Historically speaking, medicinal plants have always played an important part in human existence, and this trend dates back to ancient times. Natural compounds are now the most important source for contemporary drug development. This is due to the fact that natural compounds have the highest therapeutic selectivity, the fewest possible adverse effects, an affordable source, and may serve as lead molecules for the identification of novel medications. There is a widespread distribution of Rhynchosia species, which belong to the family Fabaceae, across the world’s tropical and subtropical regions. Some of the plants in this genus have a history of use in traditional medicine for the treatment of a variety of conditions, including those requiring an antibacterial agent, an anti-diabetic agent, an abortifacient, a wound healer, a hepatoprotective agent, or a remedy for boils, rheumatic pains, or skin infections. In this review, traditional applications of Rhynchosia species, and pharmacological activity of Rhynchosia species are compiled. It was noticed that, not enough research has been done on this genus; as a consequence, we have predicted that additional research on Rhynchosia species will likely lead to the discovery of new natural chemicals that exhibit powerful biological activity. As a result, this study could be able to provide a bird’s eye view of the future experimental research that will be carried out in the hunt for innovative drugs.